Validitas Booklet pada Materi Bakteri untuk Peserta Didik Kelas X SMA - Apriyeni, Olda; Syamsurizal, Syamsurizal; Alberida, Heffi; Rahmi, Yosi Laila (Jurnal Edutech Undiksha, 2021)
Teaching and learning activities are the most basic activities in the entire educational process. The success of learning itself depends on the use of the selected learning resources. Based on the results of the observation questionnaire learning sources in the form of textbooks, student worksheets (LKPD), PPT slides and modules are available and used in schools, but additional learning resources are still needed because the learning resources used have not been able to attract interest and increase student learning motivation . Based on this, a product was developed in the form of a booklet on material for class X SMA students that was valid and practical. The average result of the booklet validity value is 86.45% with very valid criteria with a description of 84.25% in the content feasibility aspect, 88.33% in the linguistic aspect, 86.11% in the presentation aspect, and 87.50% in the the graphic aspect. The conclusion of the research that has been done is the development of booklets on bacterial material for class X SMA students fulfills the very valid category and is very suitable for use as a learning resource.